ECONOMETRIC ANALYSIS OF INDICATORS OF SOCIO-ECONOMIC INFRASTRUCTURE AFFECTING THE ACTIVITIES OF SMALL AND MEDIUM-SIZED BUSINESS ENTITIES: https://doi.org/10.5281/zenodo.14619344 - Narkuziyev , Anvar (Science technology&Digital finance, 2025)
In this article, we will consider the analysis of several literatures on the development of infrastructure for small business and entrepreneurship in the regions of China and Turkey and the possibilities of using their experience in our country. In addition, the need to develop business infrastructure in the regions of the above-mentioned countries, its impact not only on small business and entrepreneurship, but also on the economy of the country was studied. In the article, the issue was approached with attention to the application of foreign experience in the development of business infrastructure in our country, and some aspects that should be taken into account in the development of infrastructure in the regions are cited as recommendations.